Patients without prolonged QRS after TAVI with CoreValve device do not experience high‐degree atrio‐ventricular block. Issue 5 (3rd December 2012) - Mouillet, Gauthier; Lellouche, Nicolas; Lim, Pascal; Meguro, Kentaro; Yamamoto, Masanori; Deux, Jean‐François; Monin, Jean‐Luc; Bergoënd, Eric; Dubois‐Randé, Jean‐Luc; Teiger, Emmanuel
<x xml:space="preserve">Abstract</x> Objective To identify clinical and electrical factors predicting delayed high‐degree atrio‐ventricular block (AVB) after transcatheter aortic valve implantation (TAVI). Background TAVI is a new technique for treating severe aortic valve stenosis in patients at high surgical risk but can be followed by high‐grade AVB requiring permanent pacing (PP). Methods and Results The study included 79 patients (82 ± 17 years, Euroscore = 23% ± 10%) free of PP need before and immediately after TAVI procedure. Delayed high‐degree AVB was defined by types 2 or 3 AVB diagnosed at least 24 hr after the index procedure. Permanent pacemaker implantation was performed for all these patients. We compared clinical and electrical variables before and after TAVI in patients with delayed AVB or not. TAVI was performed successfully in all patients. The 21 (26%) patients who exhibited delayed high‐grade AVB had significantly deeper prosthesis implantation (12 ± 4 mm vs. 9 ± 5 mm, P = 0.03) and wider post‐TAVI QRS duration (155 ± 17 msec vs. 131 ± 25 msec, P = 0.0004), with no difference in baseline QRS duration. Post‐TAVI QRS duration was the only independent predictor of post‐TAVI permanent for delayed high‐degree AVB (P = 0.02). After a mean follow‐up of 10 ± 8 months, all 21 patients with post‐TAVI QRS ≤128 msec were free of high‐grade AVB, whereas 21/55 (38%) patients with post‐TAVI QRS >128 msec had PP (P = 0.0016). Conclusion Delayed (>24 hr after the procedure) high‐grade AVB necessitating PP is common after TAVI. QRS duration measured immediately after TAVI was the best independent predictor of PP in this population. Patients with QRS ≤128 msec immediately after TAVI had no risk of requiring PP. © 2012 Wiley, Periodicals, Inc.